The practice of physical exercise in the cardiovascular and psychobiological health of university students (Research, Society and Development, 2022)
This study evaluated the effects of physical exercise on cardiovascular and psychobiological health (levels of anxiety, depression, fatigue) in university students. A cross-sectional study was conducted, including 72 students in the health care field in 2018. First, an anamnesis was conducted, with information on the eligibility criteria and the physical exercise they practice, to obtain the groups "practices physical exercise" and "no physical exercise." Among eligible individuals, anthropometric measurements were taken, heart rate variability was recorded, questionnaires on depression, anxiety, fatigue, and physical activity were applied, along with a cardiorespiratory test. Of the student participants, 45.0% were female, 20.0% were male, and 42 reported exercising, 30 did not. High levels of depression, anxiety, fatigue, and body fat percentage above adequate levels were observed in the study group. Students who practiced physical exercise had lower depression scores, lower body fat percentage, and better autonomic modulation when comparing study groups. There was no difference in cardiorespiratory fitness between practitioners and non-practitioners of physical exercise. A more active lifestyle, including the practice of regular physical activity, is a practical component in improving cardiometabolic and psychobiological profiles in university students and, therefore, should be encouraged during university life.